Subglottic stenosis imitating the carina – a case report of airway mimicry. Issue 1 (20th January 2021) - Trageser, H.; Lott, C.; Epp, K.; Pirlich, N.
Summary: We present a case of awake tracheal intubation with flexible bronchoscopy which resulted in incorrect tracheal tube placement. The presence of a stenotic subglottic lesion with an appearance similar to the carina led to the tube being positioned with only the tip within the trachea whilst the cuff was located between the vocal cords. A capnography trace was identified before induction of anaesthesia; however, visual confirmation of the carina was undertaken in a rushed manner due to the patient becoming agitated. Once the incorrect tracheal tube placement was identified, the decision was made to wake the patient. Thereafter, a more experienced operator successfully performed awake tracheal intubation with flexible bronchoscopy using a smaller tracheal tube, which easily passed through the subglottic stenosis. This report emphasises the importance of performing the 'two‐point check' every time awake tracheal intubation is undertaken: to confirm correct tube placement, both a capnography trace and view of the tracheal lumen including the carina and main bronchi is required. This must be properly performed before induction of anaesthesia; safety should not be compromised by a stressful environment or time pressure.